Can Knowledge Cross Boundaries - Deller, Carl (2006)
The application of knowledge is relevant to all aspects of business activity and is arguably associated with every decision taken by an organisation. It is the knowledge held, transferred and applied within a public sector organisation that will form the basis of this review.